FINANCIAL LITERACY AND FINANCIAL SELF-EFFICACY AND THEIR INFLUENCE ON RISKY CREDIT BEHAVIOR USING SHOPEE PAY LATER (STUDY ON GENERATION Z IN PEKANBARU CITY) - Damayanti, Umi Rachmah (Jurnal Al-Iqtishad, 2025)
Risky Credit Behavior refers to the use of consumer credit in ways that may negatively impact future financial stability. This study examines how financial literacy and financial self-efficacy influence risky credit behavior when using Shopee PayLater among Generation Z in Pekanbaru City. The research employs multiple linear regression analysis, including reliability and validity tests, classical assumption tests, and hypothesis testing. Using a quantitative descriptive approach, the study gathers data from 632 eligible Generation Z respondents in Pekanbaru. The results indicate that both financial literacy and self-efficacy significantly affect risky credit behavior in Shopee PayLater usage. The adjusted R-squared value of 0.105 (10.5%) suggests that these two factors explain 10.5% of the variation in risky credit behavior